Youth. The Future of Reindeer Herding Peoples. Arctic Council EALLIN Reindeer Herding Youth Project 2012-2015. - International Centre for Reindeer Husbandry (ICR); Association of World Reindeer Herders (WRH); UArctic EALÁT Institute (UEI) (Sustainable Development Working Group (SDWG), 2015)
This report is one of the deliverables to the Arctic Council Sustainable Development Working Group project 'EALLIN - The Voice of Reindeer Herding Youth 2012-2014'. The main goal of the project was to maintain and further develop a sustainable and resilient reindeer husbandry in the Arctic, working towards a vision of creating a better life for circumpolar reindeer herders. Through this project, over 160 youth from different reindeer herding peoples have had the opportunity to meet each other, learning maybe as much about themselves in the process as they learned from their peers. The material, findings and recommendations below are derived from 12 community-based workshops in Norway, Sweden and Russia, China and Mongolia, where herding youth have been both organizers and participants.